Setting-Up a Rapid SARS-CoV-2 Genome Assessment by Next-Generation Sequencing in an Academic Hospital Center (LPCE, Louis Pasteur Hospital, Nice, France) - Hofman, Paul; Bordone, Olivier; Chamorey, Emmanuel; Benzaquen, Jonathan; Schiappa, Renaud; Lespinet-Fabre, Virginie; Lanteri, Elisabeth; Brest, Patrick; Mograbi, Baharia; Maniel, Charlotte; Tanga, Virginie; Allegra, Maryline; et al. (Frontiers in Medicine, 2022)
Introduction: Aside from the RT-PCR tests for the diagnosis of the COVID-19 in routine clinical care as well as population-scale screening, there is an urgent need to increase the number and the efficiency for full viral genome sequencing in order to detect the variants of SARS-CoV-2. SARS-CoV-2 variants assessment should be easily, rapidly and routinely available in any academic hospital. Materials and Methods: SARS-CoV-2 full genome sequencing was performed retrospectively in a single laboratory (LPCE, Louis Pasteur Hospital, Nice, France) in 103 SARS-CoV-2 positive individuals. An automated workflow used the Ion Ampliseq SARS-CoV-2 panel on the Genexus Sequencer. The analyses were made from nasopharyngeal swab (NSP) (n = 64) and/or saliva (n = 39) samples. All samples were collected in the metropolitan area of Nice city (France) from September 2020 to March 2021. Results: The mean turnaround time between RNA extraction to result reports was 30 hours for each run of 15 samples. A strong correlation was noted for the results obtained between NSP and saliva paired samples, regardless of low viral load and high (>28) Ct values. After repeated sequencing runs, complete failure of obtaining a valid sequencing result was observed in 4% of samples. Besides the European strain (B.1.160), various variants were identified, including one variant of concern (B.1.1.7), and different variants under monitoring. Discussion: Our data highlight the current feasibility of developing SARS-CoV-2 next generation sequencing approach in a single hospital center. Moreover, these data showed that using the Ion Ampliseq SARS-CoV-2 Assay, the SARS-CoV-2 genome sequencing is rapid and efficient not only in NSP but also in saliva samples with a low viral load. The advantages and limitations of this setup are discussed.